Effect of the consumption of Andean crops quinoa, cañihua and tarwi on the weight increase and nitrogen retained in Wistar rats - Apaza Ahumada, Moisés Guillermo (2019)
Andean grains are an important source of macronutrients, vitamins, minerals and especially proteins. The objective of the research was to evaluate the effect of consumption of Andean quinoa crops (Chenopodium quinoa Willd), cañihua (Chenopodium pallidicaule Aellen) and tarwi (Lupinus mutabilis Sweet) on weight gain and nitrogen retained in Wistar rats. It is an experimental study, with a sample of 24 weaned male Wistar rats, they were fed with biscuits for 42 days. Three experimental flour-based cookie diets were formulated: 50% quinoa, cañihua, tarwi supplemented with 50% wheat flour and a control diet of 100% wheat flour biscuit. The weight was controlled from 21 days of age to evaluate the final weight gain and the animals were sacrificed to determine the nitrogen retained through the Kjeldahl test and additionally calculate the net utilization of proteins. Significant differences were found (p <0.05) in the weight gain between the rats fed Andean grain cookies (quinoa, cañihua and tarwi) in relation to the control group (wheat); Significant differences were found in the content of retained nitrogen and net protein utilization among the rats (p<0.05). It is concluded that the protein and nutrient content of Andean grains are better complemented with wheat flour and the consumption of biscuits formulated with these mixtures could have a positive effect on weight gain, retained nitrogen and net protein utilization.